pathos vertex semientire graph of a tree - Goudar, Venkanagouda M (International Journal of Applied Mathematical Research, 2012)
In this communications, the concept of the pathos vertex semientire graph of a tree is introduced. We present characterization of graphs whose pathos vertex semientire graph of a tree is planar, outerplanar and minimally nonouterplanar. Also we establish a characterization of graphs whose pathos vertex semientire graph of a tree is noneularian and hamiltonian.